Discoveries in Photosynthesis - Govindjee; Beatty, J.T; Gest, H.; Allen, J.F (Advances in Photosynthesis and Respiration, Including Bioenergy and Related Processes,, 2005)
"Life Is Bottled Sunshine" [Wynwood Reade, Martyrdom of Man, 1924]. This inspired phrase is a four-word summary of the significance of photosynthesis for life on earth. The study of photosynthesis has attracted the attention of a legion of biologists, biochemists, chemists and physicists for over 200 years. Discoveries in Photosynthesis presents a sweeping overview of the history of photosynthesis investigations, and detailed accounts of research progress in all aspects of the most complex bioenergetic process in living organisms. Conceived of as a way of summarizing the history of research advances in photosynthesis as of millennium 2000, the book evolved into a majestic and encyclopedic saga involving all of the basic sciences. The book contains 111 papers, authored by 132 scientists from 19 countries. It includes overviews; timelines; tributes; minireviews on excitation energy transfer, reaction centers, oxygen evolution, light-harvesting and pigment-protein complexes, electron transport and ATP synthesis, techniques and applications, biogenesis and membrane architecture, reductive and assimilatory processes, transport, regulation and adaptation, Genetics, and Evolution; laboratories and national perspectives; and retrospectives that end in a list of photosynthesis symposia, books and conferences. Informal and formal photographs of scientists make it a wonderful book to have. This book is meant not only for the researchers and graduate students, but also for advanced undergraduates in Plant Biology, Microbiology, Cell Biology, Biochemistry, Biophysics and History of Science.